Mapping emergency department asthma visits to identify poor-quality housing in New Haven, CT, USA: a retrospective cohort study. (August 2022) - Samuels, Elizabeth A; Taylor, Richard Andrew; Pendyal, Akshay; Shojaee, Abbas; Mainardi, Anne S; Lemire, Evan R; Venkatesh, Arjun K; Bernstein, Steven L; Haber, Adam L
Summary: Background: Housing conditions are a key driver of asthma incidence and severity. Previous studies have shown increased emergency department visits for asthma among residents living in poor-quality housing. Interventions to improve housing conditions have been shown to reduce emergency department visits for asthma, but identification and remediation of poor housing conditions is often delayed or does not occur. This study evaluates whether emergency department visits for asthma can be used to identify poor-quality housing to support proactive and early intervention. Methods: We conducted a retrospective cohort study of children and adults living in and around New Haven, CT, USA, who were seen for asthma in an urban, tertiary emergency department between March 1, 2013, and Aug 31, 2017. We geocoded and mapped patient addresses to city parcels, and calculated a composite estimate of the incidence of emergency department use for asthma for each parcel ( N v  ×  N p /log2 [ P ], where N v is the estimated mean number of visits per patient, N p is the number of patients, and P is the estimated population). To determine whether parcel-level emergency department use for asthma was associated with public housing inspection scores, we used regression analyses, adjusting for neighbourhood-level and individual-level factors contributing to emergency department use for asthma. Public housing complex inspection scores were obtained from standardised home inspections, which are conducted every 1–3 years for publicly funded housing. We used a sliding-window approach to estimate how far in advance of a failed inspection the model could identify elevated use of emergency departments for asthma, using the city-wide 90th percentile as a cutoff for elevated incidence. Findings: 11 429 asthma-related emergency department visits from 6366 unique patients were included in the analysis. Mean patient age was 32·4 years (SD 12·8); 3836 (60·3%) patients were female, 2530 (39·7%) were male, 3461 (57·2%) were Medicaid-insured, and 2651 (41·6%) were Black. Incidence of emergency department use for asthma was strongly correlated with lower housing inspection scores (Pearson's r =–0·55 [95% CI –0·70 to –0·35], p=3·5 × 10 −6 ), and this correlation persisted after adjustment for patient-level and neighbourhood-level demographics using a linear regression model ( r =–0·54 [–0·69 to –0·33], p=7·1 × 10 −6 ) and non-linear regression model ( r =–0·44 [–0·62 to –0·21], p=3·8 × 10 −4 ). Elevated asthma incidence rates were typically detected around a year before a housing complex failed a housing inspection. Interpretation: Emergency department visits for asthma are an early indicator of failed housing inspections. This approach represents a novel method for the early identification of poor housing conditions and could help to reduce asthma-related morbidity and mortality. Funding: Harvard-National Institute of Environmental Health Sciences (NIEHS) Center for Environmental Health.